Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/foods8010011
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Comparative Study on the Characterization of Guanidine Hydrochloride Soluble Collagen and Pepsin Soluble Collagen from the Body of Surf Clam Shell (Coelomactra antiquata)

Abstract: The aim of this study was to characterize the collagens from the body of surf clam shell (Coelomactra antiquata). Guanidine hydrochloride and pepsin were used to extract collagens. Guanidine hydrochloride soluble collagen (GSC) and pepsin soluble collagen (PSC) were separately isolated from the body of surf clam shell. Results showed that the moisture, protein, carbohydrate, and ash contents of the body of surf clam shell were 82.46%, 11.56%, 3.05%, and 2.38%, respectively, but the fat content was only 0.55%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Type I collagen is found in the cartilage of Sphyrna lewini, Dasyatis akjei, and Raja porosa [ 59 ]. In Amur sturgeon ( Acipenser schrenckii ) cartilage, type I collagen was found in acid-solubilized and salt-solubilized collagen and type II with other minor types was found in pepsin-solubilized collagen [ 26 ]. Hoki cartilage-derived collagens have been reported to have similar α chain assembly, amino acid composition, and structure to collagens in mammalian cartilage; and they could have potential in biomaterials for the treatment of cartilage-related diseases [ 60 ].…”
Section: Collagen Formation Stability and Molecular Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Type I collagen is found in the cartilage of Sphyrna lewini, Dasyatis akjei, and Raja porosa [ 59 ]. In Amur sturgeon ( Acipenser schrenckii ) cartilage, type I collagen was found in acid-solubilized and salt-solubilized collagen and type II with other minor types was found in pepsin-solubilized collagen [ 26 ]. Hoki cartilage-derived collagens have been reported to have similar α chain assembly, amino acid composition, and structure to collagens in mammalian cartilage; and they could have potential in biomaterials for the treatment of cartilage-related diseases [ 60 ].…”
Section: Collagen Formation Stability and Molecular Structurementioning
confidence: 99%
“…The low amino acid content (proline and Hyp) in marine collagen causes the low denaturation temperature, which makes fish collagen challenging to handle as it denatures at human body temperature. At present, collagen from marine invertebrate organisms is under investigation, including jellyfish and marine sponges [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish skin, scales, bone, and fins have been widely studied as alternative sources of collagen (Bae et al, 2008;Ehrlich et al, 2018;Hernández-Briones et al, 2009;Kim et al, 2016;Kim and Mendis 2006;Nomura, et al, 1995). In addition, it has been found that the mantle of scallops (Shen et al, 2007), the muscle layer of ascidians (Mizuta et al, 2002a), and the adductor of pearl oys- Shahidi et al Utilization of marine by-products for the recovery of value-added products ters (Mizuta et al, 2002b;Wu et al, 2019) can be used as new sources of collagen. Approximately, 36-54% of collagen could be obtained from fish skin, bone and fin (Nagai and Suzuki, 2000).…”
Section: Collagen and Gelatinmentioning
confidence: 99%
“…Fish skin, scales, bone, and fins have been widely studied as alternative sources of collagen (Bae et al, 2008;Ehrlich et al, 2018;Hernández-Briones et al, 2009;Kim et al, 2016;Kim and Mendis 2006;Nomura, et al, 1995). In addition, it has been found that the mantle of scallops (Shen et al, 2007), the muscle layer of ascidians (Mizuta et al, 2002a), and the adductor of pearl oys- Shahidi et al Utilization of marine by-products for the recovery of value-added products ters (Mizuta et al, 2002b;Wu et al, 2019) can be used as new sources of collagen. Approximately, 36-54% of collagen could be obtained from fish skin, bone and fin (Nagai and Suzuki, 2000).…”
Section: Collagen and Gelatinmentioning
confidence: 99%